Combining Differentiated Instruction with practices from Intercultural Education : an exploratory case study from a Finnish classroom - Nanou, Vereniki (2024)
While classrooms are becoming gradually more multicultural and multilingual, many teachers implement practices of theories like Differentiated Instruction (DI) and Intercultural Education (IE) in their teaching to cater to their students' variety of learning needs and promote equity (Valiandes, 2015). Although a lot of research has focused on both DI and IE theories, less research has been done regarding the combination of them. It has been argued that DI and IE share key elements, and complement each other. In both Finnish and broader educational contexts, a gap exists between theoretical approaches to multicultural and intercultural education and the actual practices implemented in schools. This exploratory case study investigates these implementations in a Finnish classroom through a blended DI and IE framework. Two interviews with the classroom teacher and classroom observations indicated that although the DI elements were strong, the IE elements were lacking. Themes emerging from this study highlite a variety of DI teaching practices, CLIL displays, and cooperation between the teacher and the other grade teachers as well as the parents. Regarding IE themes, the findings showed more focus on familirizing non-Finnish students with the Finnish culture, a connection between expressing culture and religion, and creating a strong teacher-student relationship and a safe and collaborative classroom environment.